The Effect of Work Factors Moderated Individual Factors on Carpal Tunnel Syndrome (CTS) in Tea Harvesters at PTPN IV Sidamanik - Rahmi Wardani; Gerry Silaban; Taufik Ashar (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The industrial sector, especially tea plants, is a sector that has a positive impact on the development of the State. However, this development is also closely related to risk factors that can lead to occupational accidents and occupational diseases that require further treatment such as Carpal Tunnel Syndrome (CTS). This study was conducted to analyze work factors moderated individual factors on CTS in tea harvesters using machines at PTPN IV Sidamanik. This study used quantitative methods of cross sectional design with Thinel test and Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) on 98 workers using correlation test and Moderated Regression Analysis (MRA). The results showed a positive relationship between work and individual factors with CTS (p value <0.05). There was an increase in R square on the interaction of work factors with individual factors by 16.3% on the age variable, 2.4% on the smoking variable and 5.7% on the Body Mass Index (BMI) variable. Individual factors (age, smoking and BMI) strengthened the influence of work factors on CTS with significance <0.05. This study is expected to provide information, input and consideration to companies in making policies regarding occupational illness, especially CTS. And can increase workers' awareness to use personal protective equipment when working and conduct an examination if they find symptoms of CTS. Keywords: Age, Body Mass Index, Carpal Tunnel Syndrome, Posture, Smoking